Performance characteristics and estimation of measurement uncertainty of two plating procedures for Listeria monocytogenes enumeration in chicken meat - Yong, W. Z.; Haresh, Kumar Kantilal; Wong, Woan Chwen; Pui, Chai Fung; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
The objectives highlighted in the present study were to determine the estimates of measurement uncertainty associated with PALCAM and CHROMagar TM Listeria media, to compare the efficacy between both media in relation to their measurement uncertainties. In addition, this study was carried out to assess the performance characteristics of spread and spiral plating procedures based on the comparison of Listeria monocytogenes enumeration between PALCAM and CHROMagar TM Listeria media. This work involved pure culture experiment, artificially contaminated samples experiment and naturally contaminated samples experiment. In pure culture experiment, PALCAM performance was relatively inferior to CHROMagar TM Listeria medium for both plating procedures. From the artificially contaminated samples, the results revealed that the values of repeatability, reproducibility, and measurement uncertainty at 95% confidence interval were comparable between both media under evaluation. However, at the level of naturally contaminated samples, the performance of CHROMagar TM Listeria medium was refutable as the presence of high number of competitive microorganisms reduced the clarity of the medium. The current emphasis in ensuring microbiological safety which requires use of accredited laboratories has led to measurable need for measurement uncertainty to ensure reliability of test results for global acceptance.